Tgfbr2 disruption in postnatal smooth muscle impairs aortic wall homeostasis - Li, Wei (American Society for Clinical Investigation, 2014)

(untitled)
TGF-β is essential for vascular development; however, excess TGF-β signaling promotes thoracic aortic aneurysm and dissection in multiple disorders, including Marfan syndrome. Since the pathology of TGF-β overactivity manifests primarily within the arterial media, it is widely assumed that suppression of TGF-β signaling in vascular smooth muscle cells will ameliorate aortic disease. We tested this hypothesis by conditional inactivation of Tgfbr2, which encodes the TGF-β type II receptor, in smooth muscle cells of postweanling mice. Surprisingly, the thoracic aorta rapidly thickened, dilated, and dissected in these animals. Tgfbr2 disruption predictably decreased canonical Smad signaling, but unexpectedly increased MAPK signaling. Type II receptor–independent effects of TGF-β and pathological responses by nonrecombined smooth muscle cells were excluded by serologic neutralization. Aortic disease was caused by a perturbed contractile apparatus in medial cells and growth factor production by adventitial cells, both of which resulted in maladaptive paracrine interactions between the vessel wall compartments. Treatment with rapamycin restored a quiescent smooth muscle phenotype and prevented dissection. Tgfbr2 disruption in smooth muscle cells also accelerated aneurysm growth in a murine model of Marfan syndrome. Our data indicate that basal TGF-β signaling in smooth muscle promotes postnatal aortic wall homeostasis and impedes disease progression.